ENHANCEMENTS IN THE MANAGEMENT OF RELATIONSHIPS WITH CUSTOMERS AS A MEANS OF PRESERVING SALES PERFORMANCE - Darlin Aulia (Universitas Dinamika, 2022)
Customer relationship management, often known as CRM and referred to in some circles as just CRM, is a strategy that allows businesses the capacity to more effectively manage their customers' accounts as well as the interactions those customers have with the business. In order for a business's CRM strategy to be successful, the organization must put a high value on the quality of the customer experience. Customers who have been loyal to a specific brand for a significant amount of time and have a high level of confidence in the company often move on to become brand advocates in other contexts. There is a chance that improvements to cross-selling, up-selling, and deep-selling might be of assistance to businesses in increasing the total lifetime worth of their clientele. Customers that consistently exhibit a commitment to the company are rewarded with a range of privileges. These might include exclusive access to sales and discounts, individualized customer support, and personalized promotions and specials. The charges that are associated to sustaining present customers are a substantial lot lower when compared to the expenditures that are involved with attracting new consumers to become clients of the business.